2013
DOI: 10.1093/rpd/nct267
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gamma radioactivity levels and associated dose rates of soil samples of the Akkuyu/Mersin using high-resolution gamma-ray spectrometry

Abstract: In this study several soil samples were collected from the Büyükeceli district where Turkey's first nuclear power plant will be built and radioactivity concentrations of (226)Ra, (232)Th, (40)K and (137)Cs were determined by gamma spectrometry using a high-purity germanium detector. The measured activity concentrations in soil samples ranged from 9.8 ± 0.7 to 258.6 ± 15.8, 11.7 ± 0.9 to 85.6 ± 5.0, 173.8 ± 2.1 to 1949.5 ± 14.7 and 0.4 ± 0.1 to 72.2 ± 2.2 Bq kg(-1) for (226)Ra, (232)Th, (40)K and (137)Cs, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…The collected core samples showed that 137 Cs concentrations were in the range of the reported values in areas located at the same latitude 30 e40 N (Karadeniz and Yaprak, 2008b and further references cited therein). The average 137 Cs concentration value (65 Bq kg À1 ) is higher than when compared with those from other parts of Turkey ( € Ozmen et al, 2014;€ Oztürk et al, 2013;Kucukomeroglu et al, 2012). On the other hand, the average concentration value obtained from this study is lower than the values reported for some other provinces of Turkey (Kurnaz et al, 2007;Celik et al, 2008).…”
Section: Resultscontrasting
confidence: 77%
“…The collected core samples showed that 137 Cs concentrations were in the range of the reported values in areas located at the same latitude 30 e40 N (Karadeniz and Yaprak, 2008b and further references cited therein). The average 137 Cs concentration value (65 Bq kg À1 ) is higher than when compared with those from other parts of Turkey ( € Ozmen et al, 2014;€ Oztürk et al, 2013;Kucukomeroglu et al, 2012). On the other hand, the average concentration value obtained from this study is lower than the values reported for some other provinces of Turkey (Kurnaz et al, 2007;Celik et al, 2008).…”
Section: Resultscontrasting
confidence: 77%
“…The detector is located in department of Physics in Akdeniz University. The energy resolution of the dedector is 1.85 keV at 1332 keV for 60 Co and 768 eV at 122 keV for 57 Co. [9,10]. Spectra of tobacco samples were obtained by using MAESTRO-32 computer program [11].…”
Section: Methodsmentioning
confidence: 99%
“…Training Center which was called IAEA 1364-43-2 in the energy range from 47 to 1836 keV by Ozmen et al (Ozmen et al 2014a(Ozmen et al , 2014b. Black and white tea samples were counted about a day using high purity germanium (HPGe) detector and a background count was taken from the detector one day without a sample to reduce the background effect of the tea samples.…”
Section: Methodsmentioning
confidence: 99%